The problems of quality education of students with disabilities: legal aspect (Pedagogy of Higher and Secondary Education, 2014)
Polgun K. V. The problems of quality education of students with disabilities: legal aspect.The problem of realization the right of people with special needs to get quality education is considered in the article. The author analyzed Ukrainian legal base in area of higher education for persons with disabilities and the legal basis of inclusive education.
Keywords: person with disabilities; the right to education; legal base; higher education; inclusive education